MECHANISMS UNDERLYING ACTION OF XINMAILONG INJECTION, A TRADITIONAL CHINESE MEDICINE IN CARDIAC FUNCTION IMPROVEMENT - Li, Zhengtao; Li, Sujuan; Hu, Lin; Li, Fang; Cheung, Alex Chun; Shao, Weizai; Que, Yuling; Leung, George Pek-heng; Yang, Cui (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: As a bioactive composite extracted from American cockroach, Xinmailong injection (XML) is used for the treatment of congestive heart failure (CHF) in China. Clinical data has provided evidence that XML has positive inotropic properties. The objective of this study was to assess the mechanisms involved in the therapeutical effect of XML on CHF. Materials and Methods: The effects of XML on the cardiac function in isolated rat heart were measured. A Ca2+ imaging technology was used in rat cardiomyocytes (H9c2 cells) to reveal the role of XML on Ca2+ channels. Meanwhile, the effects of XML on the activities of Na+/K+ ATPase and sodium/calcium exchanger were measured. In addition, the level of reactive oxygen species and the protein expressions for the superoxide dismutase and hemeoxygenase were determined in the cardiomyocytes. Results: The results showed that XML increased the electrical impulse-induced [Ca2+]i in H9c2 cells, which was dependant on extracellular Ca2+ and was abolished by ML218-HCl (a T-type Ca2+channels antagonist) but not nimodipine (a L-type Ca2+channels antagonist). Ouabain, a Na+/K+-ATPase inhibitor, increased the electrical impulse-induced [Ca2+]i, which was significantly inhibited by XML. Moreover, XML markedly inhibited the Na+/K+ ATPase activity in H9c2 cells. In addition, XML notably reduced the production of reactive oxygen species and enhanced the protein expressions of antioxidant enzymes including superoxide dismutase 1, superoxide dismutase 2 and hemeoxygenase 1 in H9c2 cell. Conclusion: Our findings pave the ways to the better understandings of the therapeutic effects of XML on cardiovascular system.